Rus Schools Established In Turkestan - Mavluda, Saxobidinova (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This thesis analyzes the history of primary and secular schools established under the Russian administration in Turkestan in the late 19th – early 20th centuries. It examines schools designed for both local and Russian populations across different regions, their organizational structures, curricula, and teacher-related issues. The study also draws on the research of M. I. Brodovskiy and N. O. Rozenbakh to discuss the effectiveness and limitations of Russian education for the local population. Findings indicate that curricula, which did not consider the mother tongue, and the insufficient linguistic preparation of teachers prevented Russian schools from achieving the expected literacy levels among the local population. Consequently, the thesis demonstrates the significance of this period as a preparatory stage for the development of Russian-native schools and later Jadid schools in the educational history of Turkestan.